2018
DOI: 10.1177/1745499918763421
|View full text |Cite
|
Sign up to set email alerts
|

An overview of e-learning in China: History, challenges and opportunities

Abstract: The Chinese government has attached great importance to the development of e-learning since its emergence in the 1990s. As a consequence of the implementation of a series of policies, China has made significant achievements in the e-learning arena with respect to infrastructure construction, production of resources, academic education, non-academic training, and education for disadvantaged groups. However, due to the constraints of China’s traditional culture, information literacy, and educational mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 3 publications
0
36
0
1
Order By: Relevance
“…For example, Kyzy et al [16] pointed out that the lack of online education experience of instructors is one important factor that may affect their use of e-learning in a blended learning context. Another study conducted by Wang et al [29] found that culture, the uneven level of information literacy, the lack of favorable e-learning environments, and the lack of_mechanisms for resources construction are the main challenges of e-learning implementation and adoption. In addition, Kisanga and Ireson [30] indicated that poor interface design and software, inadequate support, lack of knowledge, teachers' resistance to change, and other financial constraints are the main barriers for the implementation of e-learning or the adjustment of existing e-learning initiatives.…”
Section: E-learning Challenges In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kyzy et al [16] pointed out that the lack of online education experience of instructors is one important factor that may affect their use of e-learning in a blended learning context. Another study conducted by Wang et al [29] found that culture, the uneven level of information literacy, the lack of favorable e-learning environments, and the lack of_mechanisms for resources construction are the main challenges of e-learning implementation and adoption. In addition, Kisanga and Ireson [30] indicated that poor interface design and software, inadequate support, lack of knowledge, teachers' resistance to change, and other financial constraints are the main barriers for the implementation of e-learning or the adjustment of existing e-learning initiatives.…”
Section: E-learning Challenges In Developing Countriesmentioning
confidence: 99%
“…Interventions provided by the organization (to provide immediate support to both instructor and student) can potentially improve the continuity of e-learning in the higher education institutions [7], [31], [52], [53]. However, the low level of support from the university would discourage individuals from using the e-learning system [29]. The support provided for instructors could be through the provision of technical, training, motivation, and commitment to the e-learning system [54].…”
Section: ) the Type Of Support Providedmentioning
confidence: 99%
“…Age groups of 55-year-old teachers or more n = 11 (6%) of the total respondents, followed by 50-54 years, amounting to n = 9 or (5%), (45-49) years totaling n = 21 (11% ), next, followed by (40-44) years totaling n = 26 (14%), (35-39) years totaling n = 25 (14%), (30)(31)(32)(33)(34) totaling 39 (21%) and (20-24) years totaling n = 17 (9%). The teacher's working period (1-5) year is n = 74 (40%), (6-10) years is n = 51 (28%), (11)(12)(13)(14)(15) years is n = 31 (17%), (16)(17)(18)(19)(20) years totaling n = 15 (8%), (21-25) years totaling n = 2 (1%), (26-30) years totaling n = 5 (3%) and (31+) years totaling n = 7 (4%) of the total number of respondents as many as 185 people. While the biggest teacher academic qualifications are S1, which amounts to n = 153 (83%) followed by S2 totaling n = 23 (12%) and D3 totaling n = 9 (5%).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, ICT is the main key that can open the way for the global education system to improve students' knowledge and abilities. The use of ICT in education also raises a variety of learning models and methods, including network learning, multimedia education, online and open education, and blended learning [20].…”
Section: A Use Of Icts For Vocational High Schoolsmentioning
confidence: 99%
See 1 more Smart Citation